Torque ripple reduction of switched reluctance motor using fuzzy control. Issue 6 (1st August 2016) - Wang, Ming-Shyan; Chen, Seng-Chi; Fang, Wei-Chin; Chuang, Po-Hsiang
Abstract : Purpose: – Extensive efforts have been conducted on the improvement of torque ripple in switched reluctance motor (SRM) drive. The purpose of this paper is to estimate initial on time of pulse-width modulation (PWM) and turn-off angle using the motor speed and rotor angle by fuzzy logic. Design/methodology/approach: – A fuzzy logic control together with the PWM technique and turn-off angle are used to improve torque ripple and dynamic response. Findings: – After determining initial on time of PWM, the rise slope of phase current is increased. Research limitations/implications: – Future work will consider to increase the complex of the fuzzy control to adaptively tune parameters and achieve excellent results. Practical implications: – The experimental results of the proposed method are presented to show the effectiveness. Originality/value: – This paper achieves SRM control by one special PWM technique which is seldom studied.